2008
DOI: 10.5014/ajot.62.3.265
|View full text |Cite
|
Sign up to set email alerts
|

Children With Fetal Alcohol Spectrum Disorders: Problem Behaviors and Sensory Processing

Abstract: Results provide evidence that children with FASD demonstrate problem behaviors and sensory-processing impairments as reported by parents and that sensory-processing deficits co-occur with problem behaviors at a high rate in this population. This finding suggests that deficits in sensory processing may affect the ability of children with FASD to respond adaptively to their environments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
62
0
15

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(90 citation statements)
references
References 13 publications
8
62
0
15
Order By: Relevance
“…The Activities competence score in FASD was similar to comparison peers and within the "Normal" range in most studies. Somatic complaints, 14,19,35 Anxiety/depression, 14,19,35 Withdrawn/depressed, 14,19,35 Academic performance (1 study), 18 and Adaptive functioning (1 study) 18 subscale scores were similar in FASD and comparison groups, and usually within the "Normal" range (Supplemental Appendices 4 and 5).…”
Section: Presence Of An Fasd Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…The Activities competence score in FASD was similar to comparison peers and within the "Normal" range in most studies. Somatic complaints, 14,19,35 Anxiety/depression, 14,19,35 Withdrawn/depressed, 14,19,35 Academic performance (1 study), 18 and Adaptive functioning (1 study) 18 subscale scores were similar in FASD and comparison groups, and usually within the "Normal" range (Supplemental Appendices 4 and 5).…”
Section: Presence Of An Fasd Diagnosismentioning
confidence: 99%
“…After screening and review, 23 articles were included in qualitative or quantitative analysis, with between 2 and 8 articles (total: 16) included in various meta-analyses. Tables 3 and 4 show the characteristics of included studies, according to presence of FASD (10 studies) [13][14][15][16][17][18][19][20][21] or PAE (14 studies), respectively [22][23][24][25][26][27][28][29][30][31][32][33][34] : one study reported data for both PAE and FASD. 35 Most were from North America (n = 15; 65.2%), followed by Australia (n = 4) and Canada (n = 2), with 1 study each from Finland and Taiwan.…”
Section: Literature Searchmentioning
confidence: 99%
“…As desordens do espectro alcoólico fetal descrevem um termo "guardachuva" que compõem os efeitos adversos do consumo do álcool durante a gravidez, com efeitos permanentes e frequentemente devastadores para o desenvolvimento infantil (1)(2) , incluindo anomalias estruturais, comportamentais e neurocognitivas (3) . O diagnóstico clínico compõe a Síndrome Alcoólica Fetal (SAF), a síndrome alcoólica fetal parcial, a encefalopatia alcoólica e as desordens neurocomportamentais da exposição ao álcool (1) .…”
Section: Introductionunclassified
“…O diagnóstico clínico compõe a Síndrome Alcoólica Fetal (SAF), a síndrome alcoólica fetal parcial, a encefalopatia alcoólica e as desordens neurocomportamentais da exposição ao álcool (1) . O impacto teratogênico do álcool pode proporcionar déficits nas funções cognitivas, atenção, memória, processamento das informações, habilidades motoras e resolução de problemas e, desta forma, interferir no funcionamento social da criança e acarretar déficits no comportamento adaptativo, na competência social, na comunicação e nas habilidades de vida diária (1,(3)(4)(5) . Na Síndrome Alcoólica Fetal (SAF) a tríade sintomática é caracterizada por déficits de crescimento pré e pós-natais, dismorfismos faciais e evidências de anormalidades do sistema nervoso central (1)(2)(3)(4)(5)(6) .…”
Section: Introductionunclassified
See 1 more Smart Citation